Risk and protective factors in adolescent behaviour: The role of family, school and neighbourhood characteristics in (mis)behaviour among young people - Emer Smyth; Merike Darmody (The Economic and Social Research Institute (ESRI), 2021)
New research, published by the ESRI and produced in partnership with the Department of Children, Equality, Disability, Inclusion and Youth (DCEDIY), shows that schools are more important than neighbourhoods in influencing adolescent behaviour. Using data from the Growing Up in Ireland study, the findings show that most 17-year-olds have no behaviour difficulties and few consistently 'act out' at home, at school, and in the community.
Keywords: 330